2021
DOI: 10.3390/app11114756
|View full text |Cite
|
Sign up to set email alerts
|

Random-Forest Machine Learning Approach for High-Speed Railway Track Slab Deformation Identification Using Track-Side Vibration Monitoring

Abstract: High-speed railways (HSRs) are established all over the world owing to their advantages of high speed, ride comfort, and low vibration and noise. A ballastless track slab is a crucial part of the HSR, and its working condition directly affects the safe operation of the train. With increasing train operation time, track slabs suffer from various defects such as track slab warping and arching as well as interlayer disengagement defect. These defects will eventually lead to the deformation of track slabs and thus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…It generates T train sets with less samples than the original sample set. This method has been shown to improve the classification accuracy of the unstable classifiers [37,38]. T train sets are utilized to generate T decision trees.…”
Section: Random Forest Fault Diagnosis Modelmentioning
confidence: 99%
“…It generates T train sets with less samples than the original sample set. This method has been shown to improve the classification accuracy of the unstable classifiers [37,38]. T train sets are utilized to generate T decision trees.…”
Section: Random Forest Fault Diagnosis Modelmentioning
confidence: 99%
“…To verify the feasibility of this measurement method, the results from the DAS, strain gauges, and digital image correlation (DIC) were compared, which showed good consistency. Guo et al developed an intelligent detection method for track slab deformation based on a random forest model and carried out field experiments to verify it [ 56 ]. The test results showed that this intelligent algorithm can effectively identify deformations in track slabs and the recognition rate reaches 96.09%.…”
Section: Applications Of Das In Linear Infrastructure Monitoringmentioning
confidence: 99%
“…Guo et al [37] developed a fiber optic sensing-based approach for monitoring track slab deformation and an adaptive random-forest model-based technique for recognizing track slab displacement. High-speed railways (HSRs) are now being established all around the globe due to their features such as high speed, travel convenience, very low vibration, and noise.…”
Section: Literature Surveymentioning
confidence: 99%